FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PERUSAHAAN CONSUMER GOODS PERIODE 2018-2020 - Rosiana, Ester; Dermawan, Elizabeth Sugiarto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to examine and analyze the influence of asset structure, liquidity, profitability, and sales growth on debt policy in consumer goods sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The company sample in this study used purposive sampling and the selected sample was 37 consumer goods companies for the 2018-2020 period. This study uses secondary data from financial statements and techniques in data processing using multiple regression analysis and assisted by using the SPSS version 25 program. The results of this study indicate that the variables of asset structure, liquidity, profitability have a negative and significant effect on debt policy. Meanwhile, the sales growth variable has a negative and insignificant effect on debt policy.